Targeting the mTOR pathway in hepatocellular carcinoma: Current state and future trends - Matter, Matthias S. (2013)
Mechanistic target of rapamycin (mTOR) regulates cell growth, metabolism and aging in response to nutrients, cellular energy stage and growth factors. mTOR is frequently up-regulated in cancer including hepatocellular carcinoma (HCC) and is associated with bad prognosis, poorly differentiated tumors, and earlier recurrence. Blocking mTOR with rapamycin and first generation mTOR inhibitors, called rapalogs, has shown promising reduction of HCC tumors growth in preclinical models. Currently, rapamycin/rapalogs are used in several clinical trials for the treatment of advanced HCC, and as adjuvant therapy in HCC patients after liver transplantation and TACE. A second generation of mTOR pathway inhibitors has been developed recently, and is being tested in various clinical trials of solid cancers and has been used in preclinical HCC models. The results of series of clinical trials using mTOR inhibitors in HCC treatment will emerge in the near future.